Autonomic Symptoms in Older Adults Are Common and Associated With Health-Related Quality of Life - Renno-Busch, Sarah; Hildesheim, Hanna; van Uem, Janet M. T.; Sünkel, Ulrike; Röben, Benjamin; Brockmann, Kathrin; Mychajliw, Christian; Eschweiler, Gerhard W.; Berg, Daniela; Maetzler, Walter (Frontiers in Neurology, 2021)
Background: Autonomic symptoms are common in older adults, and a large body of literature focusing on age-related diseases shows that autonomic symptoms in these diseases constrain Health-Related Quality of Life (HRQoL). To our best knowledge, the association between autonomic symptoms in older adults, independent of specific diseases, and HRQoL has not yet been assessed. Aim: To assess the frequency and the effect of autonomic symptoms in general, as well as orthostatic intolerance, vasomotor, secretomotor, gastrointestinal, bladder and pupillomotor symptoms, on HRQoL in older adults. Methods: Cross-sectional data of the fourth visit of the Tübinger evaluation of Risk factors for Early detection of Neurodegeneration (TREND) study were included. Autonomic symptoms, as assessed with the Composite Autonomic Symptom Score 31 (COMPASS 31), were quantified and compared with HRQoL, as assessed with the EuroQol five-level version (EQ-5D-5L). Statistical analyses included Spearman's Rank Correlation and multiple linear regression analysis. Results: The analysis included 928 participants with a median of 68 years, 47% were women. Of those, 85% reported at least one autonomic symptom. Gastrointestinal and secretomotor symptoms were most common. The COMPASS 31 total score and all subdomains were significantly associated with reduced HRQoL. Among the subdomains, the strongest correlations with HRQoL were found for gastrointestinal and bladder symptoms. Overall, autonomic symptoms alone explained 20 percent of the variance of HRQoL; when depressive mood was added, the model explained 32 percent. Conclusion: Autonomic symptoms are associated with HRQoL and depressive symptoms in older adults.